2018
DOI: 10.3354/meps12449
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary migration of fin whales through the Strait of Gibraltar

Abstract: Fin whales Balaenoptera physalus used to be abundant in the Strait of Gibraltar and nearby Atlantic areas until their rapid collapse due to intense whaling at the beginning of the 20 th century. Recent studies seem to indicate that some fin whales, believed to belong to the North East North Atlantic (NENA) stock, now use the area to travel between the Atlantic Ocean and the Mediterranean Sea. In this study, we analyzed 15 yr of direct observations combining vessel and land-based surveys with photo-identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…II (Methods) were produced between September 2007 and April 2008, which matches the period of highest fin whale vocal activity described in the literature for the Northern Hemisphere (Watkins et al, 1987;Watkins et al, 2000;Stafford et al, 2007). It also matches the peak for the southwest Mediterranean Sea and Strait of Gibraltar, as described by Castellote et al (2012), and the peak presence in the Strait of Gibraltar as described by Gauffier et al (2018). Between May and August 2008, there were no days with high quality bouts, and automatic detections were reduced considerably.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…II (Methods) were produced between September 2007 and April 2008, which matches the period of highest fin whale vocal activity described in the literature for the Northern Hemisphere (Watkins et al, 1987;Watkins et al, 2000;Stafford et al, 2007). It also matches the peak for the southwest Mediterranean Sea and Strait of Gibraltar, as described by Castellote et al (2012), and the peak presence in the Strait of Gibraltar as described by Gauffier et al (2018). Between May and August 2008, there were no days with high quality bouts, and automatic detections were reduced considerably.…”
Section: Resultsmentioning
confidence: 58%
“…They also observed 69% of the sighted fin whales moving from the NENA toward the Mediterranean Sea between November and April. Considering the directional movements found in Gauffier et al (2018) and the seasonal presence of the acoustic characteristics found in this study, the results suggest that fin whales from the NENA may travel more frequently between the NENA and the Mediterranean Sea than Mediterranean fin whales may swim to the NENA. From the 37 bouts that were manually analyzed in this study, only four showed acoustic characteristics associated with Mediterranean fin whales.…”
Section: B Comparison With Other Studies That Characterize Notes Of mentioning
confidence: 58%
See 2 more Smart Citations
“…The Strait of Gibraltar (SoG hereafter; 36.14°N, 5.35°W; Figure 2) is the narrow and shallow oceanographic connection between the Mediterranean Sea and the Atlantic Ocean. It represents a migration bottleneck for most migratory land birds moving between the European and African continents (Miller, Onrubia, Mart, & Kaltenecker, 2016), but also for those diverse marine species moving between the Mediterranean and Atlantic water masses (Abascal, Medina, Serna, Godoy, & Aranda, 2016;Gauffier et al, 2018;Mateos-Rodríguez & Bruderer, 2012). From last century, many migratory studies used SoG as observatory point for studying spring and autumn passages of diverse marine species because individuals concentrate in a relatively small area for short periods of time, making them visible and countable on board, using radars or even using telescopes from the coast (Garcia, 1971;Hashmi & Fliege, 1994;Silvani, Gazo, & Aguilar, 1999;Stephanis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%